Accessing National Health Service Stop Smoking Services in the UK: a COM-B analysis of barriers and facilitators perceived by smokers, ex-smokers and stop smoking advisors. (June 2019) - Kwah, K.L.; Fulton, E.A.; Brown, K.E.
Abstract: Objective: Smokers who access free National Health Service (NHS) Stop Smoking Services (SSS) in the UK are four times more likely to stop smoking, yet uptake of the services has been in decline in recent years. Evidence was collated to explore the beliefs of smokers, ex-smokers and Stop Smoking Advisors (SSAs) about SSS and the barriers and facilitators to access. Study design: Mixed-methods design including i) a search of the literature; ii) a cross-sectional online questionnaire completed by 38 smokers and ex-smokers; and iii) semistructured interviews with 5 SSAs. Methods: PubMed, Web of Science, Scopus, Prospero and the NIHR Portfolio were searched in October 2017 to identify relevant studies. Smokers and ex-smokers were recruited to the online questionnaire via Public Health websites and social media in Warwickshire. SSAs identified via Public Health Warwickshire were invited to take part in an interview conducted over the telephone. Findings were collated and analysed using the COM-B ('Capability', 'Opportunity', 'Motivation' and 'Behaviour') model framework. Results: A range of practical and psychological or belief-based barriers and facilitators to accessing SSS were identified within all the components of the COM-B model, aside from physical capability, for example; 'Psychological capability', such as lack of understanding about what the service offers; 'Reflective motivation', such as lack of confidence in service efficacy; and 'Social opportunity', such as recommendations from healthcare professionals to attend. Suggestions and consideration on how future tobacco control intervention and public health messages can address these components are reported. Conclusions: Public health interventions and campaigns may benefit from focussing on addressing the well-known perceived barriers and facilitators smokers experience, in particular focussing on the components of the COM-B that have been identified as being important to increase the uptake of SSS. Highlights: Negative beliefs about Stop Smoking Services still apparent as barrier to access. All components of the COM-B model, aside from physical capability, identified as barriers. A lack of translation of evidence about barriers to service access into practice. Tobacco control policy and public health messages should attempt to address all highlighted barriers.